2013
DOI: 10.3340/jkns.2013.53.1.49
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Management of Traumatic C6-C7 Spondyloptosis

Abstract: A case of traumatic spondyloptosis of the cervical spine at the C6-C7 level is reported. The patient was treated succesfully with a anterior-posterior combined approach and decompression. The patient had good neurological outcome after surgery. A-51-year-old female patient was transported to our hospital's emergency department after a vehicle accident. The patient was quadriparetic (Asia D, MRC power 4/5) with severe neck pain. Plain radiographs, computerize tomography and spinal magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…The appropriate surgical methods are controversial, with every approach having pros and cons. However, considering the biomechanics, an initial anterior discectomy followed by a posterior reduction (if not reduced with instrumented fusion) followed an anterior fusion procedure seems to be the most appropriate as it provides the best stability and also prevents any chance of disc compression while the reduction is done in the prone position [15]. In patients in whom complete reduction is achieved, management by anterior discectomy and fusion followed by posterior instrumented fusion can be used (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate surgical methods are controversial, with every approach having pros and cons. However, considering the biomechanics, an initial anterior discectomy followed by a posterior reduction (if not reduced with instrumented fusion) followed an anterior fusion procedure seems to be the most appropriate as it provides the best stability and also prevents any chance of disc compression while the reduction is done in the prone position [15]. In patients in whom complete reduction is achieved, management by anterior discectomy and fusion followed by posterior instrumented fusion can be used (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding complications, CSF leaks due to high-grade dislocation (noniatrogenic) have been seen by few authors including us but none of the authors reported meningitis or wound leaks afterwards. 12,14 Our patient had meningitis which led to hydrocephalus and subsequent septicemia leading to death of the patient.…”
Section: Discussionmentioning
confidence: 85%
“…The most accepted approach is the combined anterior and posterior 360º or 540º, with or without corpectomies. This approach provides wide canal decompression and successful cervical spine realignment (1)(2)(3)(4)(5)(6)(7)(10)(11)(12)(13). Additionally, the management of chronic spondylisthesis would have some considerations according to our experience.…”
Section: Discussionmentioning
confidence: 99%
“…The initial management of these fractures is generally a cervical traction to achieve a closed reduction that may allow a subsequent spinal stabilization with an anterior, posterior or combined approach (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Nevertheless, in the chronic spondyloptosis (4) or high grade spondylolisthesis the treatment of the patient became a challenge to achieve a correct spinal alignment avoiding the worsening of the neurological status.…”
Section: Case Reportmentioning
confidence: 99%